(untitled) (International Journal of Mathematics and Physics, 2018)
This article evaluated the level of air pollution during the combustion of Karaganda coal in thermal power plants. The technical analysis of coal is lead and parameters of quality of coal are defined. With the use of the “Era-Air” software complex designed for solving a wide range of tasks in the area of atmospheric air protection, the complex indicators of average annual pollution in the atmosphere of the city Shakhtinsk were calculated, maximally different emissions of ash, sulfur oxides, carbon, nitrogen, resulting from the burning of Karaganda coal at thermal power plants. It is established that a complex index of pollution of atmospheric air of the city Shahtinsk more than two times higher than index of pollution, calculated for five types of pollutants. Currently available methods of reducing greenhouse gases into the atmosphere from coal combustion based on electron beam technology. Electron-beam technologies are aimed at changing the physicochemical properties of the combusted fuel with objective of increase of efficiency and completeness of coal combustion. Preliminary electron beam processing of coal leads to decrease in emissions into the atmosphere, reduces the amount of ash and slag, and reduces the maximum single-time emissions. undefined undefined Звуковая функция ограничена 200 символами Настройки : История : Обратная связь : Donate Закрыть